The counterfinancing of the net basic income in times of debt-financed relief measures during the Corona crisis - Karl Justus Bernhard Neumärker; Bianca Blum; Burhan Yalcin; Sema Yalcin (Albert-Ludwigs-Universität Freiburg, Freiburg Institute for Basic Income Studies (FRIBIS), 2021)
The measures taken to contain the Corona pandemic have resulted in, among other things, massive loss of earnings. Many people are therefore increasingly experiencing an income crisis in addition to the acute health crisis. Permanent existential insecurity remains for too many despite the numerous aid packages. The principle of need-based assistance and the determination of need for the provision of aid are proving to be insufficient. In the current crisis, earned incomes are affected most of all due to the measures taken. This leads to an asymmetric distribution of the crisis-induced burdens and thus to an asymmetric distribution of risks and burdens between performance-related and non-performance-related income, which exacerbates the redistribution in favor of capital income. The model of net basic income (NGE) shows one way to come to a solution of these problems in the crisis. Every adult person in Germany receives a monthly unconditional basic income of e.g. exteuro 550 (calculated in this approach) during the crisis period. This amount is supplemented by the suspension of rent, lease, repayment and interest obligations during this period of income loss. The amount of money paid to each person is the net share of the crisis basic income. The household savings from suspending rent, lease, principal, and interest payments is the gross. After the crisis, the NGE can be raised to a full participatory BGE of exteuro 1,200 to exteuro 1,500 as economic momentum increases. In step with this, rental, lease and capital services are to be paid again in full contract amount.
Keywords: 330